Tackling the Problem of Sensing Commonly Abused Drugs Through Nanomaterials and (Bio)Recognition Approaches - Truta, Florina; Florea, Anca; Cernat, Andreea; Tertis, Mihaela; Hosu, Oana; de Wael, Karolien; Cristea, Cecilia (Frontiers in Chemistry, 2020)
We summarize herein the literature in the last decade, involving the use of nanomaterials and various (bio)recognition elements, such as antibodies, aptamers and molecularly imprinted polymers, for the development of sensitive and selective (bio)sensors for illicit drugs with a focus on electrochemical transduction systems. The use and abuse of illicit drugs remains an increasing challenge for worldwide authorities and, therefore, it is important to have accurate methods to detect them in seized samples, biological fluids and wastewaters. They are recently classified as the latest group of “emerging pollutants,” as their consumption has increased tremendously in recent years. Nanomaterials, antibodies, aptamers and molecularly imprinted polymers have gained much attention over the last decade in the development of (bio)sensors for a myriad of applications. The applicability of these (nano)materials, functionalized or not, has significantly increased, and are therefore highly suitable for use in the detection of drugs. Lately, such functionalized nanoscale materials have assisted in the detection of illicit drugs fingerprints, providing large surface area, functional groups and unique properties that facilitate sensitive and selective sensing. The review discusses the types of commonly abused drugs and their toxicological implications, classification of functionalized nanomaterials (graphene, carbon nanotubes), their fabrication, and their application on real samples in different fields of forensic science. Biosensors for drugs of abuse from the last decade's literature are then exemplified. It also offers insights into the prospects and challenges of bringing the functionalized nanobased technology to the end user in the laboratories or in-field.